Wages and Productivity in Mexican Manufacturing - Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2014)
The author identifies the determinants of wages and productivity in Mexico over time using national representative linked employer-employee databases from the manufacturing sector. She shows that both employers and employees are benefiting from investments in education, training, work experience, foreign research and development, and openness after the North American Free Trade Agreement (NAFTA). Additional years of schooling have a higher impact on wages and productivity after NAFTA than before. Endogenous training effects are larger for productivity than for wages, suggesting that the employers share the costs and returns to training. The author also finds that investment in human capital magnifies technology-driven productivity gains. By comparing four regions of Mexico-north, center, south, and Mexico City-regional wage and productivity gaps are found to have increased over time.